PENGETAHUAN DAN KETERAMPILAN PETANI DALAM PEMANFAATAN PUPUK ORGANIK PADA TANAMAN SAYURAN DI DESA LAMOMEA KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Musafirah Amaliah Rahmah; Hartina Batoa; Salahuddin Salahuddin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
Farmers' knowledge is everything that farmers know about crop business and business opportunities or job opportunities for farmers. Farmer's skill is a knowledge communication process to change farmer's behavior to be effective, efficient and fast through technology development. Vegetables as a horticultural product is one of the main non-food sub-sectors which is very vulnerable to the use of chemicals. This study aims to find out: how is the knowledge of farmers in the use of organic fertilizers on vegetable crops in Lamomea Village, how are the skills of farmers in the use of organic fertilizers in vegetable crops in Lamomea Village and what is the relationship between the knowledge and skills of farmers and the use of organic fertilizers for vegetable crops in Lamomea Village. This research was conducted in Lamomea Village, Konda District, South Konawe Regency which was carried out from July 2022 to September 2022 with a total of 31 farmers who were respondents who were determined using the slovin formula. Data analysis in this study used quantitative methods. The results showed that the knowledge of farmers in the use of organic fertilizers in vegetable crops was in the sufficient category, while the skills of farmers in the use of organic fertilizers in vegetable crops are also in the sufficient category, Meanwhile, the relationship between knowledge and skills of farmers in the use of organic fertilizers for vegetable crops is in a very close category, significantly between the knowledge and skills of farmers in the use of organic fertilizers for vegetable crops in Lamomea Village, Konda District, South Konawe Regency.